EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN INFEKSI SALURAN KEMIH RAWAT JALAN DI RSUD PERDAGANGAN KABUPATEN SIMALUNGUN PERIODE JANUARI - MEI TAHUN 2024 - Melisa Sary Br Hutagalung,; Ismi Noer Farida,; Diyah Ayu Anggraini, (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Urinary Tract Infection (UTI) is an infection of the kidney, ureter, bladder, or urethra. UTI is more common in women than men due to anatomical differences, while in men it is often associated with factors such as an enlarged prostate or catheter use. Antibiotics are used to kill or inhibit the bacteria that cause the infection. This study aims to assess the pattern of rational antibiotic use, including appropriate therapy, appropriate patient, appropriate indication, appropriate drug, appropriate dose, and appropriate optimal treatment duration. This research method is observational with a descriptive design and retrospective data collection. This study was conducted on 50 patients with urinary tract infections. The results of this study show an evaluation of the appropriateness of antibiotic drug use obtained, namely appropriate patients with a percentage of 100%, appropriate indications 100%, appropriate drugs 100%, appropriate doses 100% and appropriate duration of treatment with a percentage of 100%.